Preparation and Evaluation of Mucoadhesive Microcapsules Employing Olibanum Resin for Controlled Release of Aceclofenac - Chowdary, K.P.R.; Madhavi, B.L.R. (Asian Journal of Chemistry, 2010)
The objective of the study is to evaluate olibanum resin, a natural resin polymer as coat for mucoadhesive microcapsules and to design mucoadhesive microcapsules of aceclofenac for controlled release. Olibanum resin coated microcapsules of aceclofenac were prepared by an emulsification-solvent evaporation method employing different proportions of core and coat and the microcapsules were evaluated for size, drug content and microencapsulation efficiency, wall thickness, surface characters by SEM, drug release kinetics and mechanism and mucoadhesiveness. The olibanum resin coated microcapsules prepared were found to be discrete, spherical, free flowing and multinucleate monolithic type. Drug content was uniform (c.v. < 1.2 %) in each batch of microcapsules and the microencapsulation efficiency was in the range 99-102.5 %. Aceclofenac release from the olibanum resin coated microcapsules was slow and spread over a period of 24 h and depended on core:coat ratio, wall thickness and size of the microcapsules. Drug release from these microcapsules was majorly by Fickian diffusion. Good linear relationships were observed between wall thickness of the microcapsules and release rate (K0) and (K1) values. In the in vitro wash-off test olibanum resin coated microcapsules exhibited good mucoadhesive property. Olibanum resin was found to be a new and an efficient microencapsulating agent for mucoadhesive microcapsules and the olibanum resin coated microcapsules were found suitable for oral controlled release of aceclofenac over 24 h.